Mapping Edutourism in Lombok: Activities, Motivations, Facilities, and Management Challenges - Arifuddin Arifuddin; I Wayan Karta; Ahmad Harjono; Murahim Murahim (Centre of Excellence in Tourism Udayana University, 2026)
Ideally, prospective visitors have comprehensive mapping about the nature of edutourism in Lombok. However, information regarding forms of edutourism, activities in the destinations, motivations of visitors and management challenges are limited. In accordance with its urgency, this current study ‘aimed’ at exploring: 1) The forms of edutourism available in Lombok; 2) facilities that supported the edutorism; 3) tourists’ motivations; and 4) management constraints and challenges. This study is a descriptive exploratory survey that maps 13 educational tourism destinations in Lombok, involving 1–2 management staff at each destination and 23 visitors (including 17 students). Data were collected through interviews, questionnaires, observations, and documentation. The data were analyzed qualitatively: Classification, coding, reduction, and synthesis to generate conclusions and destination rankings. Edutourism in Lombok reflects educative practices. Although destinations offer nature-based and cultural experiences, uneven educational facilities and limited human resources reduce their effectiveness. Tourists are motivated by both learning and leisure, while challenges such as poor infrastructure, environmental issues, and weak management hinder development. Overall, Lombok’s strong potential requires a shift toward more structured, learning-centered, and sustainable edutourism. Theoretically, this current study improves tourists’ understanding of edutourism, ranking of activities of edutourism, visitors’ motivations and management challenges. Practically, those provide a basis for innovation in edutourism activities and tourism education; expand partnerships between universities and tourism destination managers, increases socio-economic and employment opportunities; and support sustainable tourism programs. Implicationally, it requires further collaborations and management professionalism.